2011
DOI: 10.1016/j.pmrj.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Neck Flexor Endurance Test: Normative Data Scores in Healthy Adults

Abstract: Asymptomatic men displayed greater DNF endurance than women. The variability between subjects' DNF endurance capabilities was high. Age between 20 and 80 years and activity level did not affect DNF endurance. This is the first normative data set available for the DNF endurance test, which lays the foundation for further research in subjects with a history of cervicalgia and assists clinicians to objectify a milestone for DNF endurance deficits in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
7
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 35 publications
(69 reference statements)
3
63
7
3
Order By: Relevance
“…32,34 The mean change of hold time for the DCF endurance test was 22.05 seconds (¡12.8) for both groups. Fifteen of the 20 patients achieved normal hold times for the test according to Domenech et al 42 who found the average time for men and women was 38.9¡20.1 and 29.4¡13.7 seconds, respectively, in healthy adults. Finally, Stratford et al 37 reported a change score of 5 on the GROC is clinically meaningful and our patients reported a mean change score of 5.5 (¡1.1).…”
Section: Discussionmentioning
confidence: 99%
“…32,34 The mean change of hold time for the DCF endurance test was 22.05 seconds (¡12.8) for both groups. Fifteen of the 20 patients achieved normal hold times for the test according to Domenech et al 42 who found the average time for men and women was 38.9¡20.1 and 29.4¡13.7 seconds, respectively, in healthy adults. Finally, Stratford et al 37 reported a change score of 5 on the GROC is clinically meaningful and our patients reported a mean change score of 5.5 (¡1.1).…”
Section: Discussionmentioning
confidence: 99%
“…This was also stipulated to reduce the potential for physiological variability [36]. Furthermore strategies to minimise participant (and their behaviour) variability included undertaking assessments at the same time of day, and by asking participants to exercise in the same way 48 hours prior to the testing procedures to minimise both circadian variability and possible fatigue acting as confounders [37,38]. However it was not possible to control with certainty all circumstances within the human body such as pain/muscle ache, fatigue, strenuous exercise as well as perception of the testing procedure which may have had an influence on the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Physical fitness of participants were measured in five domains. 1) Neck motion was measured by a cervical range of motion goniometer (Performance Attainment Associates, US) 2) Neck flexor endurance was tested by deep neck flexor endurance test (Domenech et al 2011). 3) Neck strength was tested by biofeedback Craniocervical Flexion Test (Jull, O'leary, and Falla 2008). 4) A hand grip dynamometer(Takei A5401digital hand grip dynamometer) was used for measuring grip strength.…”
Section: Methodsmentioning
confidence: 99%